Maximizing Efficiency in Game Development Through Art Styles, AI Integration, and Creative Expression - Hemraj, Shaif (Loading)

(untitled) (Canadian Game Studies Association, 2025)
In the increasingly competitive landscape of the games industry, working efficiently is essential for ensuring products meet audience expectations and work as intended. Various elements can play a key role when attempting to develop games smoothly and successfully, as time, money and technical capabilities can be very limiting factors that can require careful consideration. For this research, this paper will explore three key examples of such elements, which are art styles, AI tools, and the role of creative expression during the development process. Each of these examples can be notable factors towards streamlining production tasks and accelerating development, which can be especially important in the fast and competitive games industry. The choice of an art style, for instance, can save time, effort and costs while also being more optimal for performance and for supporting a chosen theme. The role of creative expression is also something that should not be understated, as it can be vital for finding solutions to problems, as well as preventing other potential issues. Finally, AI tools have demonstrated significant potential and numerous possibilities to help streamline various tasks related to the games industry, such as programming, artistic production and organizing data. By analyzing these three elements—art styles, AI tools, and creative expression— this paper will aim to provide a stronger understanding of how they can contribute to ensuring a more efficient game development process.